O desenvolvimento de tecnologias viabilizadoras da energia do hidrogênio a partir do design dominante e paradigmas tecno-econômicos - Marina Domingues Fernandes (2021)
This research investigated how the techno-economic paradigms’ dynamics influenced the design of fuel cells and hydrogen technologies between the years 2000 and 2020. More specifically, the research explored the differences in design activities during the transition between the techno-economic paradigms referring to the Era of Automobile and Mass Production (4th Technological Revolution) and the Era Information and Communication (5th and current Technological Revolution). It was also investigated the differences in design activities between leading and/or rapid technological adoption countries (center) and late-comer countries (periphery). The methodological strategy adopted was a case study through a qualitative research, where the main sources of primary evidence were semi-structured, virtual and face-to-face interviews, with different agents developing fuel cells or hydrogen technologies in a global scale. The research was conducted from two theoretical lenses: dominant designs and techno-economic paradigms. Furthermore, to analyze the specificities of peripheral countries, the structuralism theory and a critical literature on global value chains supported the analysis. The results indicate that the techno-economic paradigm shift redefined the purposes of the design activities of fuel cells and hydrogen technologies. This changed the problem perceived in these activities and the set of available and competing technologies to solve it, resulting in different preferred technologic developments over time and in a technological trajectory with different characteristics from the previous one. The results also indicate an increase in the influence of the leading countries in the periphery, this especially driven by the actions of the subsidiaries of multinational companies and multilateral organizations that subsidize local governments.